2003
DOI: 10.1093/sleep/26.8.1029
|View full text |Cite
|
Sign up to set email alerts
|

Situational Insomnia: Consistency, Predictors, and Outcomes

Abstract: Normal young adults have a consistent response to various types of situational stress. Those individuals who respond with poor sleep may display increased sleepiness associated with their poor sleep but may also be more sensitive to the effects of caffeine. These individuals have cardiac changes consistent with sympathetic nervous system activation, and they may be at risk for developing insomnia and other associated disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 25 publications
7
100
0
5
Order By: Relevance
“…The present results are consistent with those of Bonnet and Arand 2003 [25], who found that subjects who had poor sleep on a laboratory adaptation night also showed consistent sleep disturbance following caffeine administration and a circadian phase-shift challenge. Our results compliment those findings using a mild stressor and show that such vulnerable individuals can be identified a priori.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present results are consistent with those of Bonnet and Arand 2003 [25], who found that subjects who had poor sleep on a laboratory adaptation night also showed consistent sleep disturbance following caffeine administration and a circadian phase-shift challenge. Our results compliment those findings using a mild stressor and show that such vulnerable individuals can be identified a priori.…”
Section: Discussionsupporting
confidence: 93%
“…The differentiation of a pharmacological from a psychological effect was not the question of the present study. However, other studies consistent with the current results suggest that the differential response is not likely due solely to a pharmacological effect [20,25]. Specifically, the current work and previous studies showing that certain 'vulnerable' individuals respond with sleep disturbance to the stress of a first-night effect, phase-shift challenges, and pharmacological challenges provide convincing evidence that this is likely a generalizable trait associated with vulnerability to multiple and distinct stressors.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations